Cyber Wellness dan Anti-Bullying: Program Pemberdayaan Remaja Desa Pasar Sungai Tanduk Kabupaten Kerinci - Yandri, Hengki; Juliawati, Dosi; Rasmita, Rasmita; Daflaini, Daflaini; Fidya, Yatti (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2025)
The rapid development of digital technology brings not only positive impacts but also new challenges for adolescents, including risks to digital mental health (cyber wellness) and increasing cases of bullying, both offline and online. In response, this Community Service Program (PkM) was designed to empower teenagers in Pasar Sungai Tanduk Village, Kerinci Regency, to become agents of change in promoting wise internet use and bullying prevention in their community. The program employed a participatory approach based on Participatory Rural Appraisal (PRA), actively involving youth in all stages of the program—from needs assessment to evaluation. A total of 30 adolescents aged 13 to 18 from diverse social, economic, and educational backgrounds participated in the activities, which were held at the Grand Mosque of Pasar Sungai Tanduk Village. The program consisted of workshops, interactive discussions, mentoring sessions, and youth-led social campaigns. Evaluation results indicated a significant improvement in participants' understanding (from an average score of 45 to 85), with 83.3% actively involved in campaign planning and execution. Furthermore, 92% reported increased confidence in identifying and reporting bullying incidents, and 88% felt more mindful in their internet usage. Notably, 70% of participants shared their knowledge within their local environment. This program successfully empowered adolescents to become more digitally aware and proactive in creating a safe and inclusive community.